Comparison of the Diagnostic Performance of qPCR, Sanger Sequencing, and Whole-Genome Sequencing in Determining Clarithromycin and Levofloxacin Resistance in Helicobacter pylori - Egli, Konrad; Wagner, Karoline; Keller, Peter M; Risch, Lorenz; Risch, Martin; Bodmer, Thomas (Frontiers in Cellular and Infection Microbiology, 2020)
Helicobacter pylori antibiotic resistance is increasing worldwide, emphasizing the urgent need for more rapid resistance detection prior to the administration of H. pylori eradication regimens. Macrolides and fluoroquinolones are widely used to treat H. pylori. In this study, we aimed to compare the diagnostic performance of A) 23SrDNA qPCR (with melting curve analysis) and an in-house developed gyrA qPCR followed by Sanger sequencing with a commercial IVD-marked hybridization probe assay (for 23SrDNA and gyrA) using 142 gastric biopsies (skipping culturing) and B) the same two qPCR for 23SrDNA and gyrA (including Sanger sequencing) with whole-genome sequencing (WGS) and phenotypic characterization of clarithromycin and levofloxacin resistance using 76 cultured isolates. The sensitivity of both qPCRs was 100% compared to that of the commercial IVD-marked hybridization probe assay for the detection of H. pylori in gastric biopsies (without resistance testing). The specificity of the qPCR gyrA followed by Sanger sequencing was 100%, indicating that the best sequence identity was always H. pylori. The results show good agreement between molecular tests, especially between qPCR (inclusive Sanger sequencing) and WGS. Discrepancies (concerning mutated or wild type of positive H. pylori gastric biopsies) were observed between Sanger sequencing of the gyrA gene and the corresponding commercial hybridization probe assay, mostly because the high sequence diversity of the gyrA gene even at positions adjacent to the relevant codons of 87 and 91 interfered with obtaining correct results from the hybridization probe assay. Interestingly, we found several mixed sequences, indicating mixed populations in the gastric biopsies (direct detection without culturing). There was a high percentage of both levofloxacin and clarithromycin resistance in gastric biopsies (both between 22% and 29%, direct detection in gastric biopsies). Therefore, we recommend analyzing both targets in parallel. We confirmed that phenotypic resistance is highly correlated with the associated mutations. We concluded that the two qPCR followed by Sanger sequencing of the gyrA gene is a fast, cost-effective and comprehensive method for resistance testing of H. pylori directly in gastric biopsies.